Contexts of Functioning of Infedinite Pronouns with –нибудь - Gazarova, Diana (Bulletin of Yerevan University H: Russian Philology, 2025)
The article examines the features of the functioning of indefinite pronouns with -нибудь. The meaning of indefiniteness is expressed by all indefinite pronouns: with –то, –нибудь, –либо, кое-, не-. However, these pronouns are not interchangeable in all cases. The choice of pronoun is influenced by various linguopragmatic factors. The article presents six main contexts in which the use of indefinite pronouns with -нибудь becomes possible: 1) sentences with probability value, 2) сonditional and interrogative sentences, 3) imperative sentences and situations related to the future plan, 4) contexts of suspended assertion and indirect negation, 5) sentences with the meaning of distributivity and multiplicity and 6) sentences with the meaning of estimation. The article examines the linguopragmatic factors that influence functioning of these indefinite pronouns. The use of indefinite pronouns with -нибудь is influenced by the presence of a meaning of an non-fixed referent. These pronouns are possible first of all in situations where the action has not been completed yet, where the probability that the action may occur is only expressed. The non-chosen, non-fixed nature of the referent makes it possible to use the pronouns we have considered in contexts with the meaning of probability, incentive to action, interrogative constructions, in situations related to the plan of the future. In contexts related to the past, the use of indefinite pronouns with -нибудь is possible only under the condition that we are talking about a multiple event, action that does not have one specific referent. Pronouns with -нибудь are capable of expressing the speaker's assessment of the object/person/phenomenon described. This is especially evident in the combination of indefinite pronouns and proper names. Contexts in which pronouns with -нибудь express the speaker's dismissive attitude are also considered.
Keywords: indefinite pronouns; reference category; estimation; indirect denial